Mental and Social Benefits from Sport Participation - Shabanski, Filip (Вісник Черкаського національного університету імені Богдана Хмельницького. Серія: "Педагогічні науки", 2016)
Maintaining a good mental health and social skills is crucial to living a healthy life, while poor mental health and lack of appropriate social behavior can prevent someone from living an enriching life. There is growing evidence that people who lack good communication skills are inclined to anti-social behaviors. Some expressions of such behaviors may include drug and alcohol abuse, domestic violation or vandalism. The recommended norms for minimum levels of physical activity in many countries have been historically based on relationships between physical activity and physicalhealth without considering the role of sports for other important elements of human well being. The aim of this article is to explore the psychological and social benefits from playing sports. The method used was the systematic review of electronic databases, which was conducted in February 2015. Studies published in the period 2009-2012 were considered for inclusion. It is concluded that in the majority of scientific publications participation in sport and physical activity is a good means for producing a range of both physical and mental benefits as well as valuable social skills